Bentuk, Kontruksi Fungsi dan Makna Mebel Antik Melayu Istana Siak - Nofrial Nofrial (Melayu Arts and Performance Journal, 2023)
Furniture is a means of supporting daily human activities, in the form of tables, chairs and so on. The tradition of using furniture also took place in Malay society in the past, including in the palace environment. This study aims to document and analyze the form, construction, function and meaning of antique Malay furniture found in the Siak Palace. Data obtained through observation and literature study. The results showed that the furniture at the Siak Palace resembled furniture developed in Europe, consisting of cupboards, tables, chairs, beds, chests, decorative glass, partitions, pendant lamps and wall lamps. Each type of furniture is divided into specific forms and functions. Furniture at the Siak Palace are generally made of wood, made as beautiful as possible with carvings, finishing and attractive accessories. The construction uses various types of wood joints, the most widely used is the interlocking joint system. The meaning of furniture in the Siak palace is related to the legitimacy of the king and the royal family, meaning the power, economic capacity, politics and social position of the royal family. Keywords: Furniture; Antique; Malay; Siak Palace  AbstrakMebel merupakan sarana pendukung aktivitas manusia sehari-hari, berupa meja, kursi dan lain sebagainya. Tradisi penggunaan mebel juga berlansung dalam masyarakat Melayu pada masa lampau, termasuk di lingkungan istana.  Penelitian ini bertujuan mendokumentasikan dan menganalisis bentuk, konstruksi, fungsi serta makna mebel antik Melayu yang terdapat di Istana Siak. Data diperoleh melalui observasi dan studi pustaka. Hasil penelitian menunjukkan mebel di Istana Siak menyerupai mebel-mebel yang berkembang di Eropa, terdiri dari lemari, meja, kursi, tempat tidur, peti, kaca hias, partisi, lampu gantung dan lampu dinding. Masing-masing jenis mebel tersebut tebagi dalam bentuk dan fungsi khusus. Mebel di Istana Siak umumnya terbuat dari bahan kayu, dibuat seindah mungkin dengan ukiran, finishing serta aksesoris yang menarik. Konstruksinya memakai bermacam tipe sambungan kayu, yang banyak digunakan adalah sistem interlocking joint. Makna mebel di istana Siak terkait dengan legitimasi raja dan keluarga istana, bermaknakan kekuasaan, kemampuan ekonomi, politik dan kedudukan sosial dari keluarga istana tersebut. Kata Kunci: Mebel; Antik; Melayu; Istana Siak